PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN DENGAN KEPEMILIKAN INSTITUSIONAL DAN KOMPENSASI EKSEKUTIF SEBAGAI VARIABEL MODERATING - Agustine, Yolanda Safira; Ratmono, Dwi (Diponegoro Journal of Accounting, 2024)
This study aims to examine the influence of corporate social responsibility (CSR) on corporate financial performance with institutional ownership and executive compensation as moderating variables. The financial performance of the company is measured using the proxy Return on Equity (ROE). This research is a quantitative study utilizing secondary data obtained through documentation techniques. The research sample consists of 45 manufacturing companies during the period from 2018 to 2020. The sample was selected using a purposive sampling method. The data analysis techniques used in this study include simple linear regression and moderated regression analysis (MRA) with the assistance of SPSS 26. The results of this study indicate that corporate social responsibility has a positive and significant effect on corporate financial performance (ROE). Meanwhile, institutional ownership and executive compensation partially cannot moderate the relationship between corporate social responsibility and corporate financial performance.